Genesis of Legal Regulation of Pre-trial Detention in Sweden and Ukraine: Comparative Analysis - Melnykova, Dariia (Journal of Legal Studies, 2023)
The paper goes on to discuss the prevalence of issues in pre-trial detention practices in both Sweden and Ukraine, as noted by international and national organizations. Sweden has witnessed a growing trend in pre-trial detention statistics, while Ukraine, despite a decreasing trend in remand, faces a substantial number of cases brought against it at the European Court of Human Rights (ECHR) pertaining to pre-trial detention. The historical context reveals that these two countries have responded differently to criticism and challenges, reflecting variations in their legal systems and corresponding regulations on pre-trial detention. Nonetheless, both nations have pursued reforms with a shared objective: to improve the pre-trial detention system. Given these divergent experiences, statistical data, and overall context, it is evident that a comparative analysis of pre-trial detention policies in Sweden and Ukraine is warranted. Such a comparison can offer valuable insights into the existing problems in both countries and suggest pertinent solutions, taking into consideration their distinctive experiences and circumstances.